Table tennis playing styles require specific energy systems demands - Milioni, Fabio [UNESP]; De Mello Leite, Jorge Vieira; Beneke, Ralph; De Poli, Rodrigo Araújo Bonetti [UNESP]; Papoti, Marcelo; Zagatto, Alessandro Moura [UNESP] (Public Library of Science (PLoS), 2018)
The aim of the present study was to investigate the differences in energy system contributions and temporal variables between offensive and all-round playing styles. Fifteen male table tennis players (Offensive players: N = 7; All-round players: N = 8) participated in the study. Matches were monitored by a portable gas analyzer and the blood lactate responses was also measured. The contributions of the oxidative (WOXID), phosphagen (WPCr), and glycolytic (W[La]) energy systems were assumed as the oxygen consumption measured during the matches above of baseline value, the fast component of excess post-exercise oxygen consumption (EPOCFAST) measured after the matches, and the net of blood lactate concentration (Δ[La]), respectively. Energy systems contributions were not significantly different between the offensive and all-round playing styles (WOXID: 96.1±2.0 and 97.0±0.6%, P = 0.86; WPCr: 2.7±1.7 and 2.0±0.6%, P = 0.13; W[La]: 1.2±0.5 and 1.0±0.7%, P = 0.95; respectively), however, magnitude-based analysis of WPCr presented Likely higher contribution for offensive compared to all-round players. Regarding temporal variables, only rate of shots presented higher values for offensive when compared to all-round players (P = 0.03), while the magnitude-based analysis presented Very likely lower, Likely lower and Likely higher outcomes of rate of shots, WPCr and maximal oxygen consumption, respectively, for all-round players. Strong negative correlation was verified for offensive players between number of shots and WPCr (r = -0.86, P = 0.01), while all-round players showed strong correlations between rally duration, WOXID (r = 0.76, P = 0.03) and maximal oxygen consumption (r = 0.81, P = 0.03). Therefore, despite no differences in energy system contributions for offensive and all-round players, different playing styles seems to requires specific energy systems demands.